Avaliação do potencial tóxico da vinhaça fitorremediada utilizando o corpo gorduroso de Rhinocricus padbergi (Diplopoda) - Garcia, Camila Fernandes Hergert [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Vinasse is one of the main residues resulting from the transformation of sugar cane into ethanol and, due to the large volume generated, researchers are seeking a suitable destination for this effluent. As an alternative to its reutilization, the fertigation in cane culture is the most used. However, its increasing use as fertilizer has generated great concern due to the adverse effects observed. With this in view, many technologies have come up with the aim of treating the vinasse and reducing its toxic potential to the environment. Among the methodologies are the Algae Area Constructed Systems (AACSs), which have aquatic macrophytes responsible for accumulating pollutants directly in their tissues and act as catalysts for purification reactions. Thus, studies assessing the treated vinasse effects by these technologies on living organisms are necessary and prudent. For this, terrestrial fauna invertebrates, such as diplopods, are one of the most appropriate organisms to evaluate the toxic effects of substances on the soil. In view of this problem, this work aimed to evaluate the vinasse toxicity after phytoremediation by water hyacinth in AACS, by means of histological and histochemical tests, analyzing the possible changes in the diplopods perivisceral fat body of the species Rhinocricus padbergi. The bioassay was performed in triplicate using two treatments: one control and one with application of phytoremediated vinasse at the maximum concentration recommended by CETESB. Twenty animals were placed in each terrarium for periods of 21 and 42 days of exposure. After exposure, three individuals from each terrarium were collected, euthanized and dissected for fat body removal. The material collected was fixed, embedded in resin and cut into a microtome for the preparation of slides for the application of histological and histochemical techniques. The results obtained by the phytoremediated vinasse physical chemical analysis showed that the...

A vinhaça é um dos principais resíduos resultantes da transformação da cana-de-açúcar em etanol e, devido ao grande volume gerado, pesquisadores estão buscando uma destinação adequada para esse efluente. Como alternativa para seu reaproveitamento, a fertirrigação na cultura da cana é a mais utilizada. Porém, seu uso crescente como fertilizante tem gerado grande preocupação devido aos efeitos adversos observados. Frente a isso, muitas tecnologias vêm surgindo com o objetivo de tratar a vinhaça e diminuir seu potencial tóxico para o ambiente. Entre as metodologias, encontram-se os Sistemas Construídos de Áreas Alagadas (SCAAs), os quais possuem macrófitas aquáticas responsáveis por acumular poluentes diretamente em seus tecidos e atuar como catalisadores para reações de purificação. Deste modo, estudos que avaliem nos organismos vivos os efeitos da vinhaça tratada por estas tecnologias são necessários e prudentes. Para isso, invertebrados da fauna terrestre, como os diplópodos, estão entre os organismos mais adequados para avaliar os efeitos de substâncias tóxicas no solo. Frente a essa problemática, este trabalho objetivou avaliar a toxicidade da vinhaça após fitorremediação por aguapé em SCAA, por meio de testes histológicos e histoquímicos analisando as possíveis alterações no corpo gorduroso perivisceral de diplópodos da espécie Rhinocricus padbergi. O bioensaio foi realizado em triplicata utilizando dois tratamentos: um controle e um com aplicação de vinhaça fitoremediada na concentração máxima recomendada pela CETESB. Foram colocados 20 animais em cada terrário por períodos de 21 e 42 dias de exposição. Após exposição, foram coletados três indivíduos de cada terrário, os quais foram anestesiados, eutanaziados e dissecados para retirada do corpo gorduroso. O material coletado foi fixado, incluído em resina e seccionado em micrótomo para confecção de lâminas para aplicação...
Keywords: Toxicidade - Testes; Vinhaça; Milípede; Resíduos sólidos; Cana-de-açúcar; Etanol; Macrófitas aquáticas; Fitorremediação; Histologia; Histoquimica; Toxicologia ambiental; Efluente - Qualidade